Age of Ultron : the junior novel - Wyatt, Chris; Whedon, Joss, 1964- (New York : Little Brown & Company, 2015)
Following the record-shattering successes of Marvel's The Avengers in 2012, The Avengers must reassemble on the big screen to combat the robotic menace of Ultron!Marvel's Avengers: Age of Ultron is set for US release on May 1, 2015.
"Based on the movie!"--Cover.
"Includes 8 pages of color photos!"--Cover.
Based on the screenplay by Joss Whedon ; produced by Kevin Feige, p.g.a. ; directed by Joss Whedon.
456
Keywords: Avengers (Fictitious characters) -- Fiction; Superheroes